2022
DOI: 10.1038/s41598-022-18394-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of personality traits and attitudes towards the rule on academic dishonesty among university students

Abstract: Academic dishonesty is becoming a big concern for the education systems worldwide. Despite much research on the factors associated with academic dishonesty and the methods to alleviate it, it remains a common problem at the university level. In the current study, we conducted a survey to link personality traits (using the HEXACO model) and people’s general attitudes towards the rule (i.e., “rule conditionality” and “perceived obligation to obey the law/rule”) to academic dishonesty among 370 university student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…According to our study’s findings, Romanian physicians demonstrate high adherence to the law and only consider a limited number of circumstances where it may be acceptable to breach legal regulations. This is particularly noteworthy given previous studies indicating that less rule-oriented individuals are more likely to engage in misconduct [ 11 , 12 , 13 ]. People who are more likely to follow the law are likewise more likely to comply with it either because they have a moral drive toward law compliance or because they generally consider unacceptable law breaches [ 14 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…According to our study’s findings, Romanian physicians demonstrate high adherence to the law and only consider a limited number of circumstances where it may be acceptable to breach legal regulations. This is particularly noteworthy given previous studies indicating that less rule-oriented individuals are more likely to engage in misconduct [ 11 , 12 , 13 ]. People who are more likely to follow the law are likewise more likely to comply with it either because they have a moral drive toward law compliance or because they generally consider unacceptable law breaches [ 14 ].…”
Section: Discussionmentioning
confidence: 71%
“…This is in contrast to the original study’s findings, which suggested that older adults tend to be more rule-oriented than their younger counterparts [ 9 ]. However, other studies have suggested that individuals may become more inclined toward engaging in illegal behavior as they age [ 11 ]. Various factors, including differences in study design, sample size, and population characteristics, may contribute to these inconsistencies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wang and Zhang (2022), correlational and SEM analyses, personality factors, and rule attitudes influence academic misconduct. Despite studies on the causes and methods of academic dishonesty, it remains a common problem in universities.…”
Section: Ai-based Assessmentsmentioning
confidence: 99%
“…Their findings underscore the pivotal role of peer influence: the higher the perceived prevalence of dishonesty within a peer group, the higher the individual propensity for such behaviours. Wang and Zhang (2022) conducted a literature review that examined the interplay between personality traits, attitudes towards norms, and academic dishonesty. They concluded that specific personality differences significantly forecast the likelihood of dishonest actions.…”
Section: Causes Of Academic Dishonestymentioning
confidence: 99%